Decrease in “Hamilton Rating Scale for Depression” Following Isotretinoin Therapy in Acne: An Open-Label Prospective Study - Gnanaraj, Pushpa (Indian J Dermatol, 2015)
BACKGROUND: Acne is a common disorder among adolescents and young adults causing a considerable psychological impact including anxiety and depression. Isotretinoin, a synthetic oral retinoid is very effective in the treatment of moderate to severe acne. But there have been many reports linking isotretinoin to depression and suicide though no clear proof of association has been established so far. OBJECTIVE: To determine whether oral isotretinoin increases the risk of depression in patients with moderate to severe acne. MATERIALS AND METHODS: One hundred and fifty patients with moderate to severe acne were treated with oral isotretinoin 0.5 mg/kg/day for a period of 3 months. Their acne and depression scoring was done at baseline and then every month for the first 3 months and then at 6 months. RESULTS: We found that the acne scoring reduced from 3.11 ± 0.49 to 0.65 ± 0.62 (P = < 0.001) at the end of 3 months. Also, the depression scoring decreased significantly from 3.89 ± 4.9 at the beginning of study to 0.45 ± 1.12 (P < 0.001) at the end of 3 months. Both the acne and depression scores continued to remain low at the end of 6 months at 0.5 ± 0.52 (P = < 0.001) and 0.18 ± 0.51 (P = < 0.001), respectively. CONCLUSIONS: Our study proves that oral isotretinoin causes significant clearance of acne lesions. It causes significant reduction in depression scores and is not associated with an increased incidence of depression or suicidal tendencies.